2022
DOI: 10.53964/jmim.2022004
|View full text |Cite
|
Sign up to set email alerts
|

Newton-GMRES Method for the Solution of Piezo-Viscous Line Contact EHL Problem with Daubechies Wavelet as a Preconditioner

Abstract: In the present paper, numerical analysis of the effect of piezo-viscous on line contact elastohydrodynamic lubrication (EHL) problem was performed. Methods:The mathematical formulation of governing equations viz. Reynolds and film thickness equations were solved using Newton-Generalized minimal residual (GMRES) method with Daubechies wavelet as preconditioner. Results:The study pertained to a wide range of parameters involved in the governing equations with the Newton-GMRES scheme, which features lower complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The procedure for the implementation of Newton-GMRES method and preconditioner is explained in detail [45]. Authors like Bujurke et al [47] and Awati et al [35] implemented the method for various EHL problems and the results agree with earlier findings.The obtained pressure values are used to calculate film thickness profiles; simultaneously with multi-level multi-integration (MLMI) method is used to obtain the solution of deformation integral. The load balance equation is verified and 0 h is corrected and again film thickness values are used to obtain new pressure values.…”
Section: Ax B Gtol Bsupporting
confidence: 59%
See 1 more Smart Citation
“…The procedure for the implementation of Newton-GMRES method and preconditioner is explained in detail [45]. Authors like Bujurke et al [47] and Awati et al [35] implemented the method for various EHL problems and the results agree with earlier findings.The obtained pressure values are used to calculate film thickness profiles; simultaneously with multi-level multi-integration (MLMI) method is used to obtain the solution of deformation integral. The load balance equation is verified and 0 h is corrected and again film thickness values are used to obtain new pressure values.…”
Section: Ax B Gtol Bsupporting
confidence: 59%
“…Zhao and Wong [34] discussed thermal EHL analysis of slip/ no-slip contact at high slide-to-roll ratio and concluded that, the combined mechanism of boundary slip and thermal effects on film formation was revealed numerically. Awati and Kumar [35] discussed the piezo-viscous EHL line contact problem by using Newton-GMRES method with Daubechies D6 wavelet as preconditioner.…”
Section: Introductionmentioning
confidence: 99%